Analyzing the Connections between Teacher Qualifications and the Availability of Trained Mathematics Teachers with Academic Performance in Public Secondary Schools in Bamenda III Subdivision, Cameroon - Nkepah , Beyoh Dieudone; Njang, Akwo Stella (Journal of Innovation in Education and Social Research, 2024)
This study seeks to explore the association between teacher qualifications, the quantity of trained mathematics educators, and students' academic achievements in public secondary schools within the Bamenda III Subdivision, Cameroon. Employing both descriptive survey and correlational research methodologies, the study population consisted of 45 mathematics teachers from the subdivision's five public secondary schools. Purposive sampling, particularly total population sampling, was utilized due to the population's small size. Data collection involved the administration of a self-designed questionnaire to mathematics teachers. Analysis encompassed both descriptive and inferential statistics, including means, correlation, coefficient of determination, p-value, and regression analysis at a significance level of 0.05. Results indicated significant correlations between mathematics teachers' qualifications, the quantity of mathematics educators in schools, and students' academic performance. The study suggests increasing the number of trained mathematics teachers through enhanced professional training and equitable distribution to schools by relevant authorities.